2010
DOI: 10.1182/blood-2009-09-238782
|View full text |Cite
|
Sign up to set email alerts
|

CD44 activation in mature B-cell malignancies by a novel recurrent IGH translocation

Abstract: Using inverse polymerase chain reaction, we identified CD44, located on chromosome 11p13, as a novel translocation partner of IGH in 9 of 114 cases of gastric, nongastric extranodal, follicular, and nodal diffuse large B-cell lymphoma (DLBCL). Notably, these translocations involving IGHS were detected in follicular lymphomas and exclusively in germinal center IntroductionMature B-cell non-Hodgkin lymphomas (NHLs) are often associated with chromosomal translocations involving IGH at chromosome band 14q32. 1-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This suggests that, in FL‐LP, cell surface CD54 could be cleaved and released as its soluble form, which would be consistent with the poorer prognosis of these patients. Recently, an enhanced proliferation rate and clonogenic capacity was found in cell lines with ectopic CD44 expression (Higashi et al , ; Hu et al , ). In our study, CD44 was also found to be more frequently expressed in patients with FL‐LP.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, in FL‐LP, cell surface CD54 could be cleaved and released as its soluble form, which would be consistent with the poorer prognosis of these patients. Recently, an enhanced proliferation rate and clonogenic capacity was found in cell lines with ectopic CD44 expression (Higashi et al , ; Hu et al , ). In our study, CD44 was also found to be more frequently expressed in patients with FL‐LP.…”
Section: Discussionmentioning
confidence: 99%
“…CD44 hypermethylation resulting in gene silencing has already been reported for other cancer types like prostate cancer and neuroblastoma [20-22]. Recently, CD44 has been shown to be a novel translocation partner of IGH in mature B-cell malignancies resulting in overexpression of CD44 lacking exon 1 [23]. …”
Section: Introductionmentioning
confidence: 98%
“…These rearrangements are erroneous byproducts of the physiological IGH recombination that occurs in normal B cells (Kuppers and Dalla-Favera, 2001). Furthermore, partner genes of IGH translocation are frequently implicated in B-cell differentiation (e.g., BCL6, IRF4, PAX5, MYC, and CD44), germinal center formation (e.g., BCL6), apoptosis (e.g., BCL2 and MALT1), and cell cycle progression (e.g., MYC, CCND1, CCND3, and CCNE1) (Willis and Dyer, 2000;Lossos, 2005;Hu et al, 2010). Hence, identifying partner genes in IGH translocation will facilitate the elucidation of developmental mechanisms involved in B-cell malignancies and may help to unravel the complexities of B lymphocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%